New taxonomic status of Foenomorpha Szépligeti as a subgenus of Capitonius Brullé (Hymenoptera: Braconidae: Cenocoeliinae) including a revision of species - Pitz, Kevin M. (Zootaxa, 2010)
Herein I describe 16 new species of Capitonius and formally transfer and redescribe the species Foenomorpha bicolor Szépligeti, F. senlura Braet and Achterberg, and F. rufa Braet and Achterberg to Capitonius as Capitonius bicolor, C. senlura, and C. rufa, new combinations. The following new species are described: Capitonius bellaptera Pitz n. sp. from Brazil, C. boringi Pitz n. sp. from South America, C. catemacoensis Pitz n. sp. from Mexico, C. flavusassumentum Pitz n. sp. from Argentina, C. lateventris Pitz n. sp. from Brazil, C. negrolabiatus Pitz n. sp. from Central and South America, C. nigrum Pitz n. sp. from South America, C. robertsonae Pitz n. sp. from Brazil, C. rondoniaensis Pitz n. sp. from Brazil, C. sarmientoi Pitz n. sp. from Colombia, C. seltmannae Pitz n. sp. from Colombia, C. sharkeyi Pitz n. sp. from Colombia, C. stramentopetiolus Pitz n. sp. from French Guyana, C. stramentosura Pitz n. sp. from Central and South America, C. venezuelaensis Pitz n. sp. from Venezuela, and C. venustus Pitz n. sp. from South America. A key to species of subgenus Foenomorpha is provided.